The versatility of RhoA activities in neural differentiation. (2nd January 2019) - Horowitz, Arie; Yang, Junning; Cai, Jingli; Iacovitti, Lorraine
ABSTRACT: In this commentary we discuss a paper we published recently on the activities of the GTPase RhoA during neural differentiation of murine embryonic stem cells, and relate our findings to previous studies. We narrate how we found that RhoA impedes neural differentiation by inhibiting the production as well as the secretion of noggin, a soluble factor that antagonizes bone morphogenetic protein. We discuss how the questions we tried to address shaped the study, and how embryonic stem cells isolated from a genetically modified mouse model devoid of Syx, a RhoA-specific guanine exchange factor, were used to address them. We detail several signaling pathways downstream of RhoA that are hindered by the absence of Syx, and obstructed by retinoic acid, resulting in an increase of noggin production; we explain how the lower RhoA activity and, consequently, the sparser peri-junctional stress fibers in Syx −/− cells facilitated noggin secretion; and we report unpublished results showing that pharmacological inhibition of RhoA accelerates the neuronal differentiation of human embryonic stem cells. Finally, we identify signaling mechanisms in our recent study that warrant further study, and speculate on the possibility of manipulating RhoA signaling in combination with other pathways to drive the differentiation of neuronal subtypes.